The Effect of Foreign Direct Investment on Labor Market Dynamics in Developing Economies (Proceeding of The International Conference on Economics and Business, 2023)
Foreign Direct Investment (FDI) plays a critical role in shaping labor market dynamics in developing economies. This paper explores the effects of FDI on job creation, wage growth, and skill development. Using empirical data from Asia and Africa, the study examines sector-specific impacts and discusses policies to maximize the benefits of FDI while mitigating potential inequalities.